The Influence of Situational Leadership and Organizational Culture on Employee Performance at PT Indoasia Raya Bersama Mojokerto - Rachmad Sayyid Jafar; Ita Rahmawati (Management and Education Journal, 2025)
This study aims to analyze the influence of situational leadership and organizational culture on employee performance at PT Indoasia Raya Bersama Mojokerto. The research employed a quantitative approach with a survey design involving 34 employees as a complete sample (saturated sampling). Data was collected using a Likert-scale questionnaire and analyzed through multiple linear regression using SPSS 27. The findings indicate that situational leadership has a significant effect on employee performance, while organizational culture shows a positive but nonsignificant effect. However, both variables simultaneously have a significant influence on employee performance, with a coefficient of determination (R²) of 0.357, indicating that situational leadership and organizational culture explain 35.7% of the variance in employee performance. These results highlight that adaptive leadership plays a dominant role in production-based work environments, whereas organizational culture needs to be strengthened to optimize its contribution to performance outcomes. This study provides practical implications for improving operational leadership competencies and enhancing cultural internalization to support sustainable employee performance improvement.